The Future of Accounting: The Impact of AI on Accounting Students' Career Prospects - Kawak, Monica Yosephina; Aprillia, Shinezia; Budisantoso, A. Totok (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study analyzes the influence of artificial intelligence (AI), technological readiness, and digital literacy on the career prospects of accounting students amid digital transformation. Employing a quantitative survey design, the research sampled 79 accounting students from various universities in Indonesia. Data were collected through questionnaires that had been tested for validity and reliability. The data analysis technique used in this study was multiple linear regression analysis in SPSS 25. The results indicate that AI has a significant effect on the career prospects of accounting students. Technological readiness and digital literacy were also found to influence students’ career prospects significantly. Thus, students’ preparedness in facing technological changes and their ability to master digital tools will enhance their competitiveness in the job market. This study makes a novel contribution by examining the relationships among AI, technological readiness, digital literacy, and the career prospects of accounting students in the context of digital transformation. It underscores the critical imporance of integrating technological adaptation into accounting curricula to prepare students for evolving industry demands.